Leaching Time and Nitric Acid Concentration Effect on the Separation of Lanthanum and Neodymium Elements from Neodymium Concentrates - Astuti, Indri Puji; Mahatmanti, F. Widhi; Setyadji, Moch.; Sudibyo, Raden (Universitas Negeri Semarang, 2021)
The process of separating the elements of lanthanum (La) and neodymium (Nd) from neodymium concentrate (Nd(OH)3) by calcination and leaching processes to determine the effect of leaching time and HNO3 concentration. The separation process begins with calcination of the Nd(OH)3 concentrate, which functions to decompose the neodymium oxide concentrate into neodymium oxide concentrate. The process was continued with leaching with variations in leaching time (5, 10, 15 and 20 minutes) using 1 M HNO3. The results of the separation of La and Nd with the optimum time were used for leaching with variations in the concentration of HNO3 (0.5, 1, 1.5 and 2 M). During the leaching process the factor that was kept constant was the ratio of sample solids to 1: 5 HNO3 solution, using room temperature and a stirring speed of 150 rpm. The La and Nd elements separated the best at a leaching time of 10 minutes and a concentration of 1 M HNO3 with the magnitude of the leaching efficiency was 63.140% and 56.238%.